Survival, cumulative hospital days and infectious complications in urgent-start PD compared with urgent-start HD - Virtanen, Jonna (Sage, 2025)
Background: Urgent-start peritoneal dialysis (PD) carries a similar efficacy and safety profile compared to urgent-start haemodialysis (HD) but is only sparsely applied due to resource issues and concerns of complication risks. Furthermore, few data exist on adverse outcomes associated with central venous catheter (CVC) insertions in urgent-start HD patients. Thus, we sought to compare patient and dialysis-related outcomes in patients undergoing urgent-start PD or HD.
Methods: All patients initiating urgent-start PD in a tertiary research hospital in 2005-2018 were included in this retrospective, single-centre, comparative study and matched with urgent-start HD patients of similar age and chronic kidney disease aetiology. All urgent-start PDs were initiated within 72 h after catheter insertion, and urgent-start HDs were performed via a CVC. All analyses were performed at 3 months and at 1 year of follow-up, respectively.
Results: Thirty-three patients who commenced urgent-start PD and 58 matched urgent-start HD control patients were included. Altogether, 26 patients (29%; PD: 36%, HD 24%) died within the 1-year follow-up, and patient survival was similar at 3 months (hazard ratio (HR): 1.15, 95% confidence interval (CI): 0.35-3.81, p = 0.82) and at 1 year of follow-up (HR: 0.64, 95% CI: 0.30-1.39, p = 0.26) between the study groups. There were no differences in the total kidney replacement therapy (KRT)-related infection rate (p = 0.66) or cumulative first-year hospital care days (p = 0.43) between the treatment groups. Altogether, 139 CVCs were inserted during the 1-year follow-up. The number of CVCs per patient was associated with the emergence of blood culture-positive bacteraemia and increased cumulative first-year hospital care days.
Conclusions: Patient survival, cumulative first-year hospital care days and total KRT-related infection rate at 3 months and 1-year follow-up are similar between urgent-start PD and urgent-start HD patients. Furthermore, CVC insertion rate is associated with incident blood culture-positive bacteraemia and increased cumulative first-year hospital care days.